(Development of Extraction Technology and Formulation of Papain as a meat Tenderizer - Junaidi, Lukman; Wijaya, Hendra; -, Mulhaqudin (Warta Industri Hasil Pertanian, 2006)
A study of development of extraction technology and formulation of papain as ameat tenderizer has been conducted.The research was conducted to evaluate some factors that influence the enzime activity i.e. active agent (Na-metabisulfit,NaCl,and mixture of Na-metabisulfit with NaCl),the amount of activating agent compare to papaya latex (2x,3x,and 4x).Observation showed that papain processed using Na-metabisulfit gave better result than papain processed using NaCl,and mixture of Na-metabisulfitwith NaCl.The result of study also showed that the amount of activating agent than give better result was 2 times of papaya latex.The activating agent concentration chosen (0,5%and 0,7%)give no significance influence to the enzyme activity of papain.The study of papain formulation as a meat tenderizer showed that formulation II (papain 10%,NaCl 50%,NaHCO3 15%,Na-citrate 10%,starch 15%)gave better result than formulation I (papain 10%,NaCl 50%,sorbitol 40%)and single formulation of papain (no added material).